2015
DOI: 10.1007/s10396-015-0637-1
|View full text |Cite
|
Sign up to set email alerts
|

Fetal diastematomyelia associated with vertebral malformation: ultrasound, MRI, and pathomorphological findings

Abstract: Using a specific clinical example, we demonstrate the ability of prenatal magnetic resonance imaging (MRI) to diagnose associated spine and spinal cord malformations in the group of spinal dysraphisms. Thus, the original ultrasound (US) and MRI results for the affected fetus at week 21 are illustrated and described in detail. The paucity of reports of prenatal MR-semiotic findings of split cord malformation comparing US and pathomorphological findings at a relatively early gestational age makes the present cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Another study of fetuses of 29 spinal muscular atrophy carrier couples at 11–14 weeks by using two-dimensional transabdominal ultrasound demonstrated that isolated lower limb movements were presented in all of them, while general movements and startle were observed in large majority of cases [ 12 ]. Weak leg movements were observed in a fetus diagnosed with diastematomyelia at 21 weeks by using dynamic-balanced-fast-filled-echo sequences cine MRI [ 41 ]. Another case study of a fetus with Déjerine–Sottas syndrome at 33 weeks found that the involvement, amplitude, and speed of the general movements and isolated leg movement were reduced [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study of fetuses of 29 spinal muscular atrophy carrier couples at 11–14 weeks by using two-dimensional transabdominal ultrasound demonstrated that isolated lower limb movements were presented in all of them, while general movements and startle were observed in large majority of cases [ 12 ]. Weak leg movements were observed in a fetus diagnosed with diastematomyelia at 21 weeks by using dynamic-balanced-fast-filled-echo sequences cine MRI [ 41 ]. Another case study of a fetus with Déjerine–Sottas syndrome at 33 weeks found that the involvement, amplitude, and speed of the general movements and isolated leg movement were reduced [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reason is that MRI of the bone is unclear, and ultrasound imaging of the fetal spinal ossification center is clearer ( 26 , 27 ). Thus, we hypothesized that prenatal ultrasound in type I longitudinal crack on spinal deformity has more advantages than fetal MRI, which are reflected in the study of Korostyshevskaya et al ( 28 ), but as a result of the longitudinal crack on the incidence of spinal cord malformation, the number of fetuses is less, with errors in the study results. This allows us to continue to collect late cases for verification.…”
Section: Discussionmentioning
confidence: 99%